The bench grafter's handbook : principles & practice - Humphrey, Brian E. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Containing 500 full color photographs and illustrations, The Bench Grafter's Handbook: Principles and Practice presents exhaustive information on all aspects of bench grafting. It details requirements of more than 200 temperate woody plant genera, covering over 2,000 species and cultivars including important ornamental, temperate fruit, and nut crops. The book explains the principles and practices of bench grafting, new procedures to enhance grafting success, and recommendations for further scientific investigation. Practical issues to aid professionals and the beginner, include detailed accounts, supported by pictures and diagrams, of the main grafting methods, knifesmanship techniques, and methods of training. Provision and design, now and for the future, of suitable structures, grafting facilities, and equipment, to provide ideal controlled environments for grafts, are described. The book describes major grafting systems, sub-cold, cold, warm, supported warm, hot-pipe, and other grafting strategies. It provides details of health and safety issues; work stations, seat design, lighting levels; recorded output figures for various types of graft; grafting knives and tools; and methods of sharpening by hand and machine. Features: Comprehensive description, pictures, and diagrams of how to learn and utilize important grafting methods. Detailed information and scientific principles behind the selection, specification, and choice of the main graft components - the rootstock and scion. Scientific principles and practicalities of providing optimal plant material, equipment, facilities and environmental conditions for graft union development including addressing the problems of graft incompatibility. Discussion of the actual and potential role of bench grafting in woody plant conservation with suggestions for new initiatives. This book is intended for use by nurserymen; those involved in the upkeep of extensive plant collections; conservationists; plant scientists; lecturers in horticulture; horticultural students; and amateurs with an interest in grafting.
OCLC-licensed vendor bibliographic record.
Keywords: Grafting; Plant propagation; TECHNOLOGY & ENGINEERING / Agriculture / General